Trajectories of cognitive decline in different types of dementia. Issue 5 (17th September 2014) - Smits, L. L.; van Harten, A. C.; Pijnenburg, Y. A. L.; Koedam, E. L. G. E.; Bouwman, F. H.; Sistermans, N.; Reuling, I. E. W.; Prins, N. D.; Lemstra, A. W.; Scheltens, P.; van der Flier, W. M.
Abstract : Background: To investigate trajectories of cognitive decline in patients with different types of dementia compared to controls in a longitudinal study. Method: In 199 patients with Alzheimer's disease (AD), 10 with vascular dementia (VaD), 26 with dementia with Lewy bodies (DLB), 20 with behavioural variant frontotemporal dementia (bvFTD), 15 with language variant frontotemporal dementia (lvFTD) and 112 controls we assessed five cognitive domains: memory, language, attention, executive and visuospatial functioning, and global cognition (Mini-Mental State Examination, MMSE). All subjects had at least two neuropsychological assessments (median 2, range 2–7). Neuropsychological data were standardized into z scores using baseline performance of controls as reference. Linear mixed models (LMMs) were used to estimate baseline cognitive functioning and cognitive decline over time for each group, adjusted for age, gender and education. Results: At baseline, patients with dementia performed worse than controls in all cognitive domains ( p < 0.05) except visuospatial functioning, which was only impaired in patients with AD and DLB ( p < 0.001). During follow-up, patients with AD declined in all cognitive domains ( p < 0.001). DLB showed decline in every cognitive domain except language and global cognition. bvFTD showed rapid decline in memory, language, attention and executive functioning (all p < 0.01) whereas visuospatial functioning remained fairly stable. lvFTD declined mostly in attention and executive functioning ( p < 0.01). VaD showed decline in attention and executive functioning. Conclusions: We show cognitive trajectories of different types of dementia. These estimations of natural disease course have important value for the design of clinical trials as neuropsychological measures are increasingly being used as outcome measures.